2021
DOI: 10.3390/ijms22147669
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Stimulates SARS-CoV-2 Internalization by Activating AhR and Increasing ACE2 Expression in Human Gingival Epithelial Cells

Abstract: A large body of evidence shows the harmful effects of cigarette smoke to oral and systemic health. More recently, a link between smoking and susceptibility to coronavirus disease 2019 (COVID-19) was proposed. COVID-19 is due to infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which uses the receptor ACE2 and the protease TMPRSS2 for entry into host cells, thereby infecting cells of the respiratory tract and the oral cavity. Here, we examined the effects of cigarette smoke on the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…Sakaguchi et al 8 Huang et al 12 Xu et al 21 Zhong et al 24 Almeida-da-Silva et al 25 Okui et al 26 Ohnishi et al 27 Periodontal tissue ACE2, Furin, and TMPRSS are expressed in periodontal tissues. SARS-CoV-2 is detected in the periodontal tissues of COVID-19 patients.…”
Section: The Oral Cavity As a Potential Reservoir For Sars-cov-2 Sali...mentioning
confidence: 99%
“…Sakaguchi et al 8 Huang et al 12 Xu et al 21 Zhong et al 24 Almeida-da-Silva et al 25 Okui et al 26 Ohnishi et al 27 Periodontal tissue ACE2, Furin, and TMPRSS are expressed in periodontal tissues. SARS-CoV-2 is detected in the periodontal tissues of COVID-19 patients.…”
Section: The Oral Cavity As a Potential Reservoir For Sars-cov-2 Sali...mentioning
confidence: 99%
“…It was found that cigarette smoke condensates upregulated ACE2 and TMPRSS2 expression in human gingival epithelial cells. Moreover, this study provided evidence that exposure to cigarette smoke condensates potentiated the internalization of a SARS-CoV-2 pseudovirus in the cells in an AhR-dependent manner (AhR is a nuclear receptor that is a known mediator of cigarette smoke responses) [35]. Thus, the experimental findings suggest that smoking cessation could reduce the susceptibility to coronavirus infection of the oral cavity structures.…”
Section: Factors Affecting Sars-cov-2 Entry Factors' Expression and T...mentioning
confidence: 65%
“…This adds to the body of growing evidence that smoking is linked to a higher chance of infection with SARS-CoV-2. One study exposed gingival epithelial cells to cigarette smoke and showed increased ACE2 and TMPRSS2, as well as increased internalisation of SARS-CoV-2 via AChR signalling, which was able to be blocked by AChR RNAi [ 72 ], showing a direct link between smoke exposure, increased ACE2 and TMPRSS2, and increased viral uptake.…”
Section: Discussionmentioning
confidence: 99%